Experimental study of sublimation drying of vegetables by applying ultra – high frequency electromagnetic waves - Meliboyev, Mirazam; Aripov, Mirolim; Kadirov, Ulugbek; Mamatov, Sherzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
consists of developing the technology of sublimation drying of vegetables in an extremely high frequency electromagnetic wave. In the article, the description of the research object, convective and sublimated drying, the modes of the initial processing process and the standard requirements for drying objects are studied in the modes of studies when the sublimated drying process is carried out in the bath. Methods for determining the quality indicators of dried foods and requirements for the quality indicators of the products under study are organoleptic assessment, humidity, restorations, dry matter content, acidity, amount of dyes, amount of vitamin "C", as well as other indicators. Organoleptic evaluation was carried out according to the indications of appearance, consistency, smell and color. The practical significance of the results of the study is explained by the fact that the selection of regime parameters of the drying process, taking into account the characteristics of vegetables, is recommended an improved technology of sublimation drying with preliminary processing in the electromagnetic wave range of extremely high frequencies.